Rancang Bangun Sistem Pengukur Suhu Tubuh Manusia Jarak Jauh Berbasis Internet of Things (IOT) - Nuri Afriani, Eka; Djatmiko, Wisnu; Bintoro, Jusuf (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2023)
This research aims to design and build a remote human body temperature measuring system based on the Internet of Things (IoT) as an effort to prevent the spread of COVID-19. This system utilizes the MLX90614 sensor as a non-contact body temperature detector, the ESP-32 CAM microcontroller as a data processing and information delivery center, and integration with the Telegram application for remote notifications. The measurement results are also displayed via a 16x2 LCD, with a buzzer and LED indicator as a marker of body temperature conditions. If the body temperature exceeds 37.5 °C, the buzzer and red LED are active, while temperatures below 35 °C trigger the blue LED. Tests show that the system works well and has a high level of accuracy, with an average measurement error of 0.438% compared to the standard Infrared Thermometer SK-T008 thermometer. These results prove that the developed IoT-based temperature measuring system is effective, accurate, and reliable for remote health monitoring.